Acute life‐threatening massive haemoptysis in a patient with a predicted difficult airway and emphysematous lung disease. Issue 2 (29th October 2018) - Adlakha, Amit; Capel, Ifor; Addala, Dinseh; Davis, Peyton; Wong, Adrian
Summary: A 61‐year‐old male presented to the emergency department with acute life‐threatening massive haemoptysis. His previous history was remarkable for extensive mandibular and retromolar resection and reconstruction for squamous cell carcinoma ten years previously. A recent computed tomography scan of the thorax showed severe bullous emphysema. There were several features suggestive of a difficult airway, such as reduced mouth opening and fixed neck flexion. A technique was required, therefore, that avoided the use of a double‐lumen tube or bronchial blocker. We report the successful use of a post‐carinal Aintree intubation catheter to facilitate oxygenation of the right lung with a concurrent bronchially‐advanced single‐lumen tracheal tube to isolate and ventilate the left lung. This temporising strategy successfully bridged the life‐threatening phase of acute haemoptysis and the patient later received definitive treatment for a newly‐identified right upper lobe adenocarcinoma.